The Juridical Analysis of Inheritance Rights for Second Class Heirs in Religious Courts - Muhammad Ramadhani Citrawan; Aryani Witasari (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2022)
This research aims to know, analyze, and examine the juridical analysis of inheritance rights for heirs of the second class in the Surakarta Religious Court.Approach method in this researchused namely normative juridical or called doctrinal law or library research. Named doctrinal legal research because this research is only shown to written regulations so this research is closely related to the library because it will require secondary data from the librarythe required data includes secondary data obtained from library materials that provide an explanation of primary legal materials such as laws, research results, or legal expert opinions. the method of data analysis uses descriptive normative which provides an overview based on the results of an analysis of inheritance rights for heirs of the second class in the Religious CourtsBased on the results of the research and discussion, it was concluded that the right to inherit for heirs of the second class at the Surakarta Religious Court was based on the judge's considerations in deciding case Number: 228 /P dt.P/2021/PA.Ska in determining the heirs had referred to the Compilation of Islamic Law this is in accordance with the theory of Islamic justice and Pancasila, and the theory of legal protection according to Satjipto Raharjo.